Diplomatic response to global health challenges in recognizing patient needs: A qualitative interview study - Karačić Zanetti, Jasna; Brown, Matthew; Viđak, Marin; Marušić, Ana (Frontiers in Public Health, 2023)
Background Global health diplomacy is the applied practice of foreign affairs to further national goals that focus on health issues requiring international cooperation and collective action. We aimed to determine how international diplomats and health policy-related professionals in the EU understand the concept of health diplomacy, which impacts both diplomatic relations as well as patients' rights. Methods In a qualitative interview study, we used a heterogeneous stratified purposeful sampling to reach participants from different countries and different practitioners from the Pyramid of Health Diplomacy: core, multi-stakeholder, and informal. Reflexive thematic analysis was used to identify the main themes. Findings We contacted 131 practitioners of GHD, of which 37 responded, and nine agreed to be interviewed. From 11 interview questions, four main themes emerged from the analysis of the individual interview. The participants reported limited knowledge about the definition of GHD but also that they engaged in daily activities and decisions of inter-governmental bodies. They were not aware of existing special education and training for health attachés and made suggestions for improving the field and practice of GHD. They were not fully familiar with the European Charter of Patients' Rights. There was a consensus from all participants that patient rights need to improve as a fundamental right. They stressed the fact that the hospital lockdown and the right access to healthcare were impaired during the COVID pandemic. Interpretation The role of health diplomacy in linking public health and foreign affairs is key to respecting patients' rights. Health over other interests is becoming an increasingly critical element in foreign policy. Establishing a clear career path for health attachés is necessary to foster effective global health agreements and coordination across countries.